THE INFLUENCE OF PROFESSIONALISM, WORK CULTURE, AND DISCIPLINE ON SERVICE PERFORMANCE IN SIDOARJO REGENCY WITH APPRECIATION AS AN INTERVENING VARIABLE - Heru Susanto; Sriyono (International Journal of Economic Integration and Regional Competitiveness, 2026)
Objective: This study aims to analyze the effect of professionalism, work culture, and discipline on service performance, both directly and indirectly through the appreciation variable among public service employees in Sidoarjo Regency. Method: The data were collected through questionnaires distributed to 212 respondents during the period of December 2025 to January 2026, and then analyzed using the SEM-PLS method with the assistance of SmartPLS 3.0. Results: The results indicate that all variables have a positive and significant effect on service performance, with the highest coefficient values shown by work culture (0.326) and professionalism (0.311). The R Square value for service performance is 0.632, indicating that the model falls into a moderate to strong category. In addition, appreciation is proven to play a significant mediating role, although the indirect effects are relatively smaller, such as the relationship between work culture and service performance through appreciation (0.075). The NFI value of 0.819 suggests that the model has an acceptable level of fit. Novelty: Overall, these findings confirm that improving service performance is not only influenced by individual factors but is also strengthened by appreciation mechanisms within the organization.